Web 2.0-based collaborative learning framework promoting lifelong learning: developing sustainability competencies - Ataie, Farib; Shah, Asadullah; Bagheri, Fatemeh; Imtiaz Ali, Najma; Mohammadgholipour, Maryam; Rezaie, Behzad; Shaikh, Humaiz (Science Publishing Corporation Inc, 2018)
This paper aims to present a Web 2.0-based collaborative Learning framework based on the social constructivist theory promoting life-long learning. The Web 2.0 provides conditions of collaborative learning, multiple modes and methods of learning and multiple perspec-tive to achieve learning goals. This practical framework under the guidelines of design science research methodology allows learners to actively engage in the learning process, construct own knowledge and use to solve real-world problems collaboratively. Experts reviewed and confirmed the validity of the framework. Three successive iterations, working with 42 students in formal learning and Facebook members in informal learning were conducted to demonstrate and validate how learners started developing critical thinking, self-regulation and use of knowledge. The framework contributes to the practice of lifelong learning with emphasis on developing sustaina-bility competencies that enable learners to gain more skills in applying different problem-solving frameworks to complex daily life prob-lems.